Loss of long‐chain acyl‐CoA synthetase isoform 1 impairs cardiac autophagy and mitochondrial structure through mechanistic target of rapamycin complex 1 activation. Issue 11 (28th July 2015) - Grevengoed, Trisha J.; Cooper, Daniel E.; Young, Pamela A.; Ellis, Jessica M.; Coleman, Rosalind A.
ABSTRACT: Because hearts with a temporally induced knockout of acyl‐CoA synthetase 1 ( Acsl1 T ‐/‐ ) are virtually unable to oxidize fatty acids, glucose use increases 8‐fold to compensate. This metabolic switch activates mechanistic target of rapamycin complex 1 (mTORC1), which initiates growth by increasing protein and RNA synthesis and fatty acid metabolism, while decreasing autophagy. Compared with controls, Acsl1 ‐/‐ hearts contained 3 times more mitochondria with abnormal structure and displayed a 35‐43% lower respiratory function. To study the effects of mTORC1 activation on mitochondrial structure and function, mTORC1 was inhibited by treating Acsl1 ‐/‐ and littermate control mice with rapamycin or vehicle alone for 2 wk. Rapamycin treatment normalized mitochondrial structure, number, and the maximal respiration rate in Acsl1 hearts, but did not improve ADP‐stimulated oxygen consumption, which was likely caused by the 33‐51% lower ATP synthase activity present in both vehicle‐ and rapamycin‐treated Acsl1 T ‐/‐ hearts. The turnover of microtubule associated protein light chain 3b in Acsl1 T ‐/‐ hearts was 88% lower than controls, indicating a diminished rate of autophagy. Rapamycin treatment increased autophagy to a rate that was 3.1‐fold higher than in controls, allowing the formation of autophagolysosomes and the clearance of damaged mitochondria. Thus, long‐chain acyl‐CoA synthetase isoform 1 (ACSL1) deficiency in the heart activated mTORC1, thereby inhibiting autophagy and increasing the number of damaged mitochondria.—Grevengoed, T. J., Cooper, D. E., Young, P. A., Ellis, J. M., Coleman, R. A. Loss of long‐chain acyl‐CoA synthetase isoform 1 impairs cardiac autophagy and mitochondrial structure through mechanistic target of rapamycin complex 1 activation. FASEB J. 29, 4641‐4653 (2015). www.fasebj.org